Factors influencing Brazilian value investing portfolios - Holloway, Pedro (2013)
This study contributes to research on value investing in Brazil analyzing the Brazilian funds that adopt this philosophy. The goal is to identify some of the factors that influence the decisions of value investing managers to maintain an asset in their portfolios. The results point out that the variables that influence portfolio managers to maintain a stock in their assets under management are greater stability in earnings per share high ROA (Return on Assets) high gross margin company size and liquidity of the shares.